2022
DOI: 10.1093/jee/toac166
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Protocol for CRISPR/Cas9-Mediated Gene Knockout in Tephritid Fruit Flies Led to the Recreation of White Eye and White Puparium Phenotypes in the Melon Fly

Abstract: Tephritid fruit flies are among the most invasive and destructive agricultural pests worldwide. Over recent years, many studies have implemented the CRISPR/Cas9 genome-editing technology to dissect gene functions in tephritids and create new strains to facilitate their genetics, management, and control. This growing literature allows us to compare diverse strategies for delivering CRISPR/Cas9 components into tephritid embryos, optimize procedures, and advance the technology to systems outside the most thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
4
16
1
Order By: Relevance
“…Based on full-length cDNA, Bdorwp is highly similar to other wp proteins reported in insects. 36 Loss of function for Bdorwp induces disruption of pupae pigmentation in adult B. dorsalis and showed an obvious phenotype of white pupae, consistent with previous reports. 17 Aside from the pupa pigmentation, Bdorwp also strongly regulated several reproductive behaviors, such as courtship, copulation, and oviposition.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on full-length cDNA, Bdorwp is highly similar to other wp proteins reported in insects. 36 Loss of function for Bdorwp induces disruption of pupae pigmentation in adult B. dorsalis and showed an obvious phenotype of white pupae, consistent with previous reports. 17 Aside from the pupa pigmentation, Bdorwp also strongly regulated several reproductive behaviors, such as courtship, copulation, and oviposition.…”
Section: Discussionsupporting
confidence: 91%
“…In tephritids, MFS orthologues control white pupae phenotype in med fly C. capitata and 17 melon fly B. cucurbitae, 36 and in this study were shown to control the oriental fruit fly, B. dorsalis. Moreover, orthologues of white pupae are present in 146 of 148 insect species aggregated and are single copies in 133 species.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The CRISPR/Cas9 system is a straightforward and effective genome‐editing method with tremendous potential for genetic modification and investigating gene function in species beyond model insects (Ashok et al, 2023; Choo et al, 2018; Wang et al, 2017). Several Tephritid genomes have been edited using this method (Bai et al, 2019; Koidou et al, 2020; Li & Handler, 2019; Meccariello et al, 2017; Paulo et al, 2022; Sim et al, 2019; Zhao et al, 2019). The current investigation concentrated on the role of the white gene in B. dorsalis .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to do in‐depth research on the pest, particularly at the molecular level, using the recently developed technology. Of late, genetic biocontrol achieved through gene drive mediated by CRISPR/Cas9 is gaining momentum for designing an effective area‐wide pest management strategy for several pests such as Aedes aegypti (Li et al, 2017), Anopheles gambiae (Galizi et al, 2016; Hammond et al, 2016), Drosophila suzukii (Li and Scott, 2016), Ceratitis capitata (Meccariello et al, 2017), Zeugodacus cucurbitae (Paulo et al, 2022), Bactrocera tryoni (Choo et al, 2018), B. oleae (Koidou et al, 2020) that include B. dorsalis (Bai et al, 2019; Zhao et al, 2019). The above approach, called the precision‐guided sterile insect technique (pgSIT), has been successfully demonstrated in Drosophila melanogaster (Kandul et al, 2019), which is yet to be validated in pests of agricultural importance.…”
Section: Introductionmentioning
confidence: 99%